From By-Products to Promising Bifunctional Food Ingredients: Physicochemical Characterization and Antioxidant and Emulsifying Improvement Evaluation Based on the Synergy of Phenolic Acids, Flavonoids and Tannins with Bovine Liver Hydrolysates - Yufeng Duan; Xue Yang; Ruheng Shen; Li Zhang; Xiaotong Ma; Yuling Qu; Long He; Lin Tong; Guangxing Han (Foods)
In recent years, bifunctional ingredients extracted and utilized from waste by-products as raw materials have received significant attention in the food production process. Previous studies have found that bovine livers possess both antioxidant and emulsifying potential; therefore, enhancing these dual properties is a current research focus. In this study, three different types of polyphenols (epigallocatechin gallate [EGCG], gallic acid [GA] and tannin [TA]) provide a reference on how to achieve better complexation of polyphenols with bovine liver hydrolysates (BLHs). Based on the molecular weight results, it was shown that the bovine liver peptides bind to polyphenols to form complexes with higher molecular weights. Furthermore, the binding affinities among the three complexes were as follows: TA > EGCG > GA. The emulsions stabilized by the coupling compounds contained more homogeneous and dense droplets (optical microscopy). Both the antioxidant properties and the emulsifying activity of all complexes were superior to those of bovine liver hydrolysates (BLHs) (p < 0.05), confirming synergistic effects that either flavonoids, phenolic acids or tannins possess with bovine liver hydrolysates. This combination provides an effective strategy for developing novel foods with specific functions.